Electrospun Polyaniline-Based Composite Nanofibers: Tuning the Electrical Conductivity by Tailoring the Structure of Thiol-Protected Metal Nanoparticles. (14th September 2017) - Pierini, Filippo; Lanzi, Massimiliano; Nakielski, Paweł; Kowalewski, Tomasz Aleksander
Abstract : Composite nanofibers made of a polyaniline-based polymer blend and different thiol-capped metal nanoparticles were prepared using ex situ synthesis and electrospinning technique. The effects of the nanoparticle composition and chemical structure on the electrical properties of the nanocomposites were investigated. This study confirmed that Brust's procedure is an effective method for the synthesis of sub-10 nm silver, gold, and silver-gold alloy nanoparticles protected with different types of thiols. Electron microscopy results demonstrated that electrospinning is a valuable technique for the production of composite nanofibers with similar morphology and revealed that nanofillers are well-dispersed into the polymer matrix. X-ray diffraction tests proved the lack of a significant influence of the nanoparticle chemical structure on the polyaniline chain arrangement. However, the introduction of conductive nanofillers in the polymer matrix influences the charge transport noticeably improving electrical conductivity. The enhancement of electrical properties is mediated by the nanoparticle capping layer structure. The metal nanoparticle core composition is a key parameter, which exerted a significant influence on the conductivity of the nanocomposites. These results prove that the proposed method can be used to tune the electrical properties of nanocomposites.